UMP’s Strategic Plan on glory by design - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) will continue to reinforce its education, research and service to world class standard and by doing it in a more creative and innovative engineering and technology ecosystem, one that will benefit the people and country.